2022
DOI: 10.3389/fpubh.2022.904985
|View full text |Cite
|
Sign up to set email alerts
|

Family economic hardship and adolescent mental health during the COVID-19 pandemic

Abstract: ObjectiveThis study examined whether pandemic related family economic hardships influenced adolescents' mental health during the COVID-19 pandemic in Korea.MethodsData were collected from 54,948 adolescents who participated in the 2020 Korea Youth Risk Behavior Web-Based Survey. We performed a multiple logistic regression analysis to examine the association between family economic hardship and mental health (anxiety, depressive symptoms, and suicidal ideation).ResultsAmong the adolescents, 39.7, 24.7, and 5.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Another predictor of depression as evident in this study was studying without a scholarship. Unexpected financial insecurity has indulged university students in an unpleasant milieu that affects their psychological well-being (Aslan, Ochnik, & Çınar, 2020; Kim et al ., 2022). University students who were previously working to pay their tuition fees as well as supporting their family can hardly manage these expenses in this unprecedented time which might be one of the probable reasons behind this association (Islam et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another predictor of depression as evident in this study was studying without a scholarship. Unexpected financial insecurity has indulged university students in an unpleasant milieu that affects their psychological well-being (Aslan, Ochnik, & Çınar, 2020; Kim et al ., 2022). University students who were previously working to pay their tuition fees as well as supporting their family can hardly manage these expenses in this unprecedented time which might be one of the probable reasons behind this association (Islam et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, financial difficulties can have an impact on the family dynamics and relationships, which are crucial for adolescents' well-being (van Harmelen et al ., 2016). Ample studies have shown that the current pandemic has brought financial constraints on families resulting in negative connotations on students’ health (Andrade, Gillen, Molina, & Wilmarth, 2022; Kim et al ., 2022; Rodrigues, Silva, & Franco, 2021). Students’ perceive a lack of family support due to frustration and unfriendly home environment which makes them reluctant to vent out their feelings leading to poor mental health tendencies (Yu et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mental Health Professional School Outreach Project provided a great amount of support to children and adolescents who experienced mental health issues while attending school. For instance, children who experienced deterioration in their home environment or domestic discord in isolated households due to the COVID-19 pandemic experienced deterioration in their mental health during the pandemic [ 53 ] and were not adequately treated due to parental apathy or negative perceptions of mental health care and treatment. The Mental Health Professional School Outreach Project improved student and caregiver awareness through school visitation projects and positively influenced school staff awareness and capacity-building.…”
Section: Mental Health Of Children and Adolescents And Mental Health ...mentioning
confidence: 99%
“…In the first scheme (cumulative risk) as the number of stressors/adverse experiences increase so does the risk of developing psychopathology. With this model one considers the number of pandemic related stressors youth may have coped with in addition to forced isolation, such as loss of a loved one (Hillis et al, 2021) or financial insecurity (Kim et al, 2022). For instance, for low-income families, COVID-19 resulted in increases in food insecurity (Fang et al, 2022) which became an additional stressor both for families and their children and a factor in their mental health (Fang et al, 2021).…”
Section: Taking a Broad View Of Covid-19 Stressors And Youth Mental H...mentioning
confidence: 99%